Are Smoking Cessation Treatments Associated with Suicidality Risk? An Overview - J. Kim Penberthy; J. Morgan Penberthy; Marcus R. Harris; Sonali Nanda; Jennifer Ahn; Caridad Ponce Martinez; Apule O. Osika; Zoe A. Slepian; Justin C. Forsyth; J. Andrew Starr; Jennifer E. Farrell; Joshua N. Hook (SAGE Publishing, 2016)
Risk of suicidality during smoking cessation treatment is an important, but often overlooked, aspect of nicotine addiction research and treatment. We explore the relationship between smoking cessation interventions and suicidality and explore common treatments, their associated risks, and effectiveness in promoting smoking reduction and abstinence. Although active smokers have been reported to have twofold to threefold increased risk of suicidality when compared to nonsmokers, 1 4 research regarding the safest way to stop smoking does not always provide clear guidelines for practitioners wishing to advise their patients regarding smoking cessation strategies. In this article, we review pharmacological and cognitive behavioral therapy (CBT) options that are available for people seeking to quit smoking, focusing on the relationship between the ability of these therapies to reduce smoking behavior and promote abstinence and suicidality risks as assessed by reported suicidality on validated measures, reports of suicidal ideation, behaviors, actual attempts, or completed suicides. Pharmacotherapies such as varenicline, bupropion, and nicotine replacement, and CBTs, including contextual CBT interventions, have been found to help reduce smoking rates and promote and maintain abstinence. Suicidality risks, while present when trying to quit smoking, do not appear to demonstrate a consistent or significant rise associated with use of any particular smoking cessation pharmacotherapy or CBT/contextual CBT intervention reviewed.